2020
DOI: 10.1103/physrevb.101.054507
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic signatures of domain walls in s+is and s+id superconductors: Observability and what that can tell us about the superconducting order parameter

Abstract: One of the defining features of spontaneously broken time-reversal symmetry (BTRS) is the existence of domain walls, the detection of which would be strong evidence for such systems. There is keen interest in BTRS currently, in part, due to recent muon spin rotation experiments, which have pointed towards Ba 1−x K x Fe 2 As 2 exhibiting a remarkable case of s-wave superconductivity with spontaneously broken time-reversal symmetry. A key question, however, is how to differentiate between the different theoretic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
(105 reference statements)
2
5
0
Order By: Relevance
“…Hence, excitations that are commonly associated with purely the matter fields, such as domain walls and defects, in s+is and s+id models will exhibit a spontaneous magnetic response. This confirms previous numerical calculations that have been performed for domain walls 34 . It has been suggested that defects do not produce spontaneous magnetic field in such models 38 .…”
Section: Introductionsupporting
confidence: 92%
See 4 more Smart Citations
“…Hence, excitations that are commonly associated with purely the matter fields, such as domain walls and defects, in s+is and s+id models will exhibit a spontaneous magnetic response. This confirms previous numerical calculations that have been performed for domain walls 34 . It has been suggested that defects do not produce spontaneous magnetic field in such models 38 .…”
Section: Introductionsupporting
confidence: 92%
“…The twisting angle is given in Eq. 35 and determines the amount the local magnetic field twists away from the external field direction. We have also plotted the normalised energy density F = F − F 0 , the condensate densities ρ 1 ,ρ 2 and phase difference θ 12 = θ 1 − θ 2 .…”
Section: Meissner State Resultsmentioning
confidence: 99%
See 3 more Smart Citations